Tantangan Penegakan Hukum Peradilan Pajak Terhadap Industri Rokok Ilegal dI Indonesia - Aulana, Muhammad Saukhan; Salsabila, Aulia; Hardini, Farantika Dwi; Aji, Azahra Wulandari; Putra, Aditya Amarta (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The enforcement of tax justice laws against the illegal cigarette industry in Indonesia is an increasingly urgent issue in line with the increasing practice of tax smuggling and evasion. This article aims to analyze the challenges faced by law enforcement officials in tackling the illegal cigarette industry, as well as its impact on state revenue and public health. Through a qualitative approach, this study. Collected data from various sources, including journal articles, government reports, and relevant current news. The analysis showed that the main challenges include weak inter-agency coordination, lack of trained human resources, and corruption that hampers the effectiveness of law enforcement. In addition, socio-economic factors also play an important role in exacerbating the situation. This research is expected to provide recommendations for policymakers to improve law enforcement strategies and create a more conducive environment for the legal tobacco industry.